Clinical isolates of Trichophyton rubrum are completely inhibited by photochemical treatment with a γ‐cyclodextrin formulation of curcuminoids. Issue 4 (4th February 2020) - Brasch, Jochen; Beck‐Jendroschek, Vera; Walther, Grit; Rubbel, Darian
Summary: Introduction: It was shown previously that dermatophytes can markedly be inhibited by a photochemical treatment with curcumin. This kind of photo‐inactivation needs to be improved, however, because curcumin is poorly water‐soluble. Therefore, a new water‐soluble γ‐cyclodextrin formulation of curcuminoids was tested for its photochemical inactivation of Trichophyton ( T . ) rubrum . Materials and methods: Conidia were harvested from 6 typical strains of T rubrum and used to inoculate wells of microtiter plates. These wells were also filled with a γ‐cyclodextrin curcuminoid formulation with 0.1% DMSO and Sabouraud broth. The assays were then irradiated with visible light (wavelength 420 nm, 45 J/cm 2 ). After 24 hours, curcuminoid was added once more, and irradiation was repeated. Fungal growth was monitored photometrically for 8 days and compared with controls. Results: Growth of all 6 T rubrum strains was completely inhibited by the photochemical treatment with the γ‐cyclodextrin formulation of curcuminoids. The same curcuminoid formulation applied without irradiation had only a minor inhibitory effect. Discussion: Photo‐inactivation of dermatophytes with a γ‐cyclodextrin formulation of curcuminoids plus visible light is a very promising procedure with potential for a new treatment of patients with superficial tinea.